Study on Microstructure and Properties of the UV Curing Acrylic Epoxy/SiO2 Nanocomposite Coating. (29th October 2021) - Nguyen, Ngoc Linh; Dang, Thi My Linh; Nguyen, Tuan Anh; Ha, Hoang Thu; Nguyen, Thien Vuong
Abstract : This study is aimed at exploring the effects of SiO2 nanoparticles on the crosslinking and mechanical and thermal properties of UV curing acrylic epoxy coating. The curing polymerization process and thermal and mechanical properties of UV-curable acrylate epoxy system have been evaluated with or without the presence of SiO2 nanoparticles. To fabricate the UV curing acrylic epoxy/SiO2 nanocomposite coating, nano-SiO2 particles (0.5–5 wt.% by weight of resin) were added in the photo-curable system using sonication for 3 h. Various techniques for characterization have been used, such as FESEM (field emission scanning electron microscope), FTIR (Fourier-transform infrared spectroscopy), TGA (thermogravimetry analysis), gel fraction, and swelling degree analyses. FESEM data indicated that at the content of 2.5 wt.%, nanosilica was homogeneously dispersed in the coating procedure. However, once added 5 wt.%, large aggregation portions were found inside the coating matrices. Surprisingly, nano-SiO2 could play dual roles, as both UV absorbers and nanoreinforcers, in this nanocomposite coating. Besides, data from FTIR, gel fraction, and swelling degree analyses confirmed the role of SiO2 nanoparticles as UV absorbers that reduced the conversion performance of acrylate double bonds, thus increased slightly the swelling degree of coating. In addition, incorporation of SiO2 nanoparticles (as nanofillers, at content of 2.5 wt.%) in the polymer matrix enhanced significantly the abrasion resistance and thermal stability of the coating, by 60% (from 98.3 to 158.4 lite/mil) and 9°C (from 348°C to 357°C), respectively.